Ketahanan Nasional Dalam Perspektif Al-qur’an - Ghani, Abdul (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
The conclusion of this dissertation is that the concept of national resilience in the Qur'an supports the National Resilience concept of national resilience, which consists of 8 (eight) gatra, namely: geography, demographics, ideology, politics, economics, social culture, and natural resources. Besides that, through searching the words al-difa '(defense), al-amn (security), al-hifz (maintenance) and al-salam (safety in the Qur'an, this dissertation reveals 9 (nine) other gatras that support the national resilience, namely: conducive community environmental resilience, the community's physical and mental health, the quality of education, law enforcement, deliberative culture, technology, national character, leadership and faith of citizens.This disertation has different studies with Syarifuddin (2018):